The use of Nanotrap particles in the enhanced detection of Rift Valley fever virus nucleoprotein. - Nazly Shafagati; Lindsay Lundberg; Alan Baer; Alexis Patanarut; Katherine Fite; Benjamin Lepene; Kylene Kehn-Hall (PLoS ONE, 2015)
Rift Valley fever virus (RVFV) is a highly pathogenic arthropod-borne virus that has a detrimental effect on both livestock and human populations. While there are several diagnostic methodologies available for RVFV detection, many are not sensitive enough to diagnose early infections. Furthermore, detection may be hindered by high abundant proteins such as albumin. Previous findings have shown that Nanotrap particles can be used to significantly enhance detection of various small analytes of low abundance. We have expanded upon this repertoire to show that this simple and efficient sample preparation technology can drastically improve the detection of the RVFV nucleoprotein (NP), the most abundant and widely used viral protein for RVFV diagnostics.After screening multiple Nanotrap particle architectures, we found that one particle, NT45, was optimal for RVFV NP capture, as demonstrated by western blotting. NT45 significantly enhanced detection of the NP at levels undetectable without the technology. Importantly, we demonstrated that Nanotrap particles are capable of concentrating NP in a number of matrices, including infected cell lysates, viral supernatants, and animal sera. Specifically, NT45 enhanced detection of NP at various viral titers, multiplicity of infections, and time points. Our most dramatic results were observed in spiked serum samples, where high abundance serum proteins hindered detection of NP without Nanotrap particles. Nanotrap particles allowed for sample cleanup and subsequent detection of RVFV NP. Finally, we demonstrated that incubation of our samples with Nanotrap particles protects the NP from degradation over extended periods of time (up to 120 hours) and at elevated temperatures (at 37ºC).This study demonstrates that Nanotrap particles are capable of drastically lowering the limit of detection for RVFV NP by capturing, concentrating, and preserving RVFV NP in clinically relevant matrices. These studies can be extended to a wide range of pathogens and their analytes of diagnostic interest.